a unusual case of de novo CD5-positive brain diﬀuse large B-cell lymphoma coexpressing MYC and BCL2 - Barrionuevo, Carlos (2019)
Diffuse large B-cell lymphoma is a rare neoplasm of the central nervous system with aggressive behavior and poor outcome. CD5 expression in nodal or extranodal in this neoplasm is infrequent. These cases tend to be more aggressive than the CD5 negative cases. Herein, we report a case of primary brain CD5-positive diffuse large B-cell lymphoma presenting in an immunocompetent 64-year-old woman. She presented with intensity frontoparietal headache, nausea, vomiting, generalized seizures and confusional symptoms. Nuclear magnetic resonance showed characteristics of malignant lymphoma. The patient received treatment with corticoids with good response. Two years after the initial condition, she presented symptoms again. Brain images studies showed bifrontal neoplasm. No tumors were found in other sites. On the basis of morphology and immunohistochemistry, the diagnosis was CD5-positive diffuse large B-cell lymphoma. The present case confirms in this neoplasm multiple pathways are altered. Its identification can be used as therapeutic targets.